2017
DOI: 10.18203/2319-2003.ijbcp20174365
|View full text |Cite
|
Sign up to set email alerts
|

The role of antioxidants and free radicals in the healing effects of Bacopa monniera on acetic acid-induced colitis in rats

Abstract: Background: The aim to study and elucidate the healing effects of ethanolic extract of dried whole plant of Bacopa monniera against experimental colitis in rats.Methods: Bacopa monniera whole plant extract was administered orally, once daily for 14 days, to rats after induction of colitis with acetic acid. We studied its effects on: faecal output, food and water intake, and body weight changes and also examined colonic mucosal damage, inflammation and status of antioxidants: superoxide dismutase, reduced gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Ulcerative colitis was experimentally provoked in the current study by transrectal instillation of acetic acid (5% v/v), similar to the procedure agreed by another author [30] who used acetic acid to stimulate an experimental example of UC The UC group (group II) in the current experiment exhibited ulceration, damaged crypts with widespread neutrophil infiltration and congested blood vessels. Also, Statistically, this was established by significant decrease in the mean area % of alcian blue stained goblet cells when compared with (group I), significant increase in the area% of TNF-α expression when compared to control group and significant decrease in area % of the immunopositive nuclei for PCNA reaction compared to (group I).…”
Section: Discussionmentioning
confidence: 60%
“…Ulcerative colitis was experimentally provoked in the current study by transrectal instillation of acetic acid (5% v/v), similar to the procedure agreed by another author [30] who used acetic acid to stimulate an experimental example of UC The UC group (group II) in the current experiment exhibited ulceration, damaged crypts with widespread neutrophil infiltration and congested blood vessels. Also, Statistically, this was established by significant decrease in the mean area % of alcian blue stained goblet cells when compared with (group I), significant increase in the area% of TNF-α expression when compared to control group and significant decrease in area % of the immunopositive nuclei for PCNA reaction compared to (group I).…”
Section: Discussionmentioning
confidence: 60%
“…Currently, a common animal model used for inducing UC involves the intrarectal injection of 4% acetic acid with a contact time ranging from 15 to 30 seconds with the colon. The examination of the pharmacological effects of chemical substances occurs within 24 hours after induction, with various treatment periods (42)(43)(44)(45)(46). Our previous study identified an optimal model, involving 10 minutes of 4% acetic acid contact, UC confirmation, initiation of treatment 72 Jundishapur J Nat Pharm Prod.…”
Section: Discussionmentioning
confidence: 99%